(untitled) (Revista Ifes Ciência, 2017)
This paper presents an efficient method to measure real-world distance between interest points of a 3-D objectusing a camera, two laser distance sensors and Image Processing techniques. This method consists of calculating the distance between interest points of an object in the image plane. Two laser distance sensors placed next to the camera measure accurately the distance between the camera and the object. Moreover, the laser dots generated by the distance sensors are visible in the image, acting as a reference along with the distance measures in the calculations. As a result, thecalculation of the interest point's coordinate on the camera 3-D space is transformed in a real-world distance between interest points. Through a set of experiments, we show that the proposed system measures distancesup to 70 mm with sub-mm accuracy. The results suggest a potential use of our method in many other Computer Vision applications, including industrial applications.